Psychiatric Stigma in Treatment-Seeking Adults with Personality Problems: Evidence from a Sample of 214 Patients - Catthoor, Kirsten; Schrijvers, Didier; Hutsebaut, Joost; Feenstra, Dineke; Sabbe, Bernard (Frontiers in Psychiatry, 2015)
Stigmatization is a major hindrance in adult psychiatric patients with Axis-I diagnoses, as shown consistently in most studies. Significantly fewer studies on the emergence of psychiatric stigma in adult patients with personality disorders exist, although the resulting evidence is conclusive. Some authors consider patients with personality disorders at risk for severe stigmatization because of intense difficulties during interpersonal contact, even in a psychotherapeutic relationship. The aim of this study was primarily the assessment of pre-existing stigma in patients referred for intensive treatment for personality disorders. The study enrolled 214 patients admitted to the adult department of a highly specialized mental health care institute offering psychotherapy for patients with severe and complex personality pathology. All patients underwent a standard assessment with self-report questionnaires and a semi-structured interview to measure Axis II personality disorders. The Stigma Consciousness Questionnaire (SCQ) and the Perceived Devaluation-Discrimination Questionnaire (DDQ), both validated instruments, were used to measure perceived and actual experiences of stigma. Independent sample t-tests were used to investigate differences in the mean total stigma scores for patients both with and without a personality disorder. One-way ANOVA’s were performed to assess the differences between having a borderline personality disorder, another personality disorder, or no personality disorder diagnosis.Multiple regression main effect analyses were conducted in order to explore the impact of the different personality disorder diagnosis on the level of stigma. The mean scores across all patient groups were consistent with rather low stigma. No differences were found for patients with or without a personality disorder diagnosis. Level of stigma in general was not associated with an accumulating number of personality disorders.